Translation of an evidence-based virtual reality simulation-based interprofessional education into health education curriculums: An implementation science method. (March 2022) - Liaw, Sok Ying; Ooi, Sim Leng; Mildon, Robyn; Ang, Emily Neo Kim; Lau, Tang Ching; Chua, Wei Ling
Abstract: Background: The development of interprofessional competencies through an evidence-based program is paramount to nurture a collaborative practice-ready workforce for patient-centered care and safety. Aims: To describe an implementation science approach for translation of an evidence-based virtual reality simulation-based interprofessional education (VR-Sim-IPE) program into medical and nursing curriculums, and to evaluate the implementation outcomes. Methods: Implementation strategies from the "Expert Recommendations for Implementing Change" were used to support implementation of the VR-Sim-IPE program. This included recruiting and training 28 practicing clinicians as facilitators to deliver the program to 599 medical and nursing students. Proctor's conceptual framework for implementation outcomes was applied with multiple data collection methods to evaluate the VR-Sim-IPE program. An online survey was administered to measure the levels of acceptability, appropriateness, feasibility, and adoption. Forty-four sessions of structured observations were carried out to examine the facilitators' implementation fidelity. Individual interviews were conducted with 15 facilitators to identify the facilitators and barriers to the program implementation. An implementation cost analysis was also conducted. Results: Both facilitators and students had positive perceptions of the acceptability, adoption, appropriateness, and feasibility of the VR-Sim-IPE program. Facilitators were observed to implement the program with high fidelity, including program adherence, dosage, quality of delivery, and student responsiveness. While opportunities to contribute and learn, as well as receiving training and support, were identified as facilitators to implementation, the lack of familiarity with the virtual environment, varying levels of student participation, and facilitating interprofessional groups were reported barriers. The implementation costs amounted to USD45, 648.50. Conclusion: The evaluation of implementation outcomes identifies strategies for future implementation that could potentially enhance program acceptance, reduce implementation cost, improve penetration, and achieve program sustainability. These include increasing facilitation group size, preparing students to be active participants, and incorporating interprofessional facilitation skills in facilitators' training. Highlights: Implementation science method can be applied to support the translation of evidence-based program into curriculums. The implementation strategies facilitate the integration of interprofessional competencies into curriculums. The evaluation of implementation outcomes enabled the identification of future implementation strategies.